Use of micro computed-tomography and 3D printing for reverse engineering of mouse embryo nasal capsule - Kaiser, Markéta; Zikmund, Tomáš; Kaucká, Markéta; Adameyko, Igor; Jaroš, Josef; Paloušek, David; Škaroupka, David; Kaiser, Jozef (IOP Publishing, 2016)
Imaging of increasingly complex cartilage in vertebrate embryos is one of the key tasks of developmental biology. This is especially important to study shape-organizing processes during initial skeletal formation and growth. Advanced imaging techniques that are reflecting biological needs give a powerful impulse to push the boundaries of biological visualization. Recently, techniques for contrasting tissues and organs have improved considerably, extending traditional 2D imaging approaches to 3D. X-ray micro computed tomography (uCT), which allows 3D imaging of biological objects including their internal structures with a resolution in the micrometer range, in combination with contrasting techniques seems to be the most suitable approach for non-destructive imaging of embryonic developing cartilage. Despite there are many software-based ways for visualization of 3D data sets, having a real solid model of the studied object might give novel opportunities to fully understand the shape-organizing processes in the developing body. In this feasibility study we demonstrated the full procedure of creating a real 3D object of mouse embryo nasal capsule, i.e. the staining, the CT scanning combined by the advanced data processing and the 3D printing.

Imaging of increasingly complex cartilage in vertebrate embryos is one of the key tasks of developmental biology. This is especially important to study shape-organizing processes during initial skeletal formation and growth. Advanced imaging techniques that are reflecting biological needs give a powerful impulse to push the boundaries of biological visualization. Recently, techniques for contrasting tissues and organs have improved considerably, extending traditional 2D imaging approaches to 3D. X-ray micro computed tomography (uCT), which allows 3D imaging of biological objects including their internal structures with a resolution in the micrometer range, in combination with contrasting techniques seems to be the most suitable approach for non-destructive imaging of embryonic developing cartilage. Despite there are many software-based ways for visualization of 3D data sets, having a real solid model of the studied object might give novel opportunities to fully understand the shape-organizing processes in the developing body. In this feasibility study we demonstrated the full procedure of creating a real 3D object of mouse embryo nasal capsule, i.e. the staining, the CT scanning combined by the advanced data processing and the 3D printing.
Use of micro computed-tomography and 3D printing for reverse engineering of mouse embryo nasal capsule
Keywords: Computerized Tomography (CT) and Computed Radiography (CR); Image reconstruction in medical imaging; Multi-modality systems; Computerized Tomography (CT) and Computed Radiography (CR); Image reconstruction in medical imaging; Multi-modality systems